Studi Kasus Pengelolaan Destinasi Wisata dalam Analisis SWOT pada Desa Wisata Batulayang - Veronique, Azela Veronique; Soeprapto, Vishnuvardhana S. (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This research contains a SWOT (Strength, Weakness, Opportunity, Threat) analysis which was carried out at the Batulayang Tourism Village, precisely in Cisarua District, Bogor Regency. SWOT analysis (Strength, Weakness, Opportunity, Threat) is a method of identifying several factors systematically in order to formulate a strategy for a bureaucracy. SWOT analysis also has an IFAS (Internal Factor Analysis Strategic) matrix where IFAS is a calculation made to determine how weak or strong a company's internal conditions are. Meanwhile, the EFAS Matrix (External Factor Analysis Strategic) is a calculation to find out how the Company responds to its external conditions. After calculating each matrix, the weights of each matrix will be entered into the IE (Internal & External) matrix. This research is qualitative research which aims to determine management based on SWOT analysis. In this research, the resource persons consisted of the Head of Batulayang Village, the Secretary of Batulayang Tourism Village, and also visitors. This research resulted in a score of 2.91 on the IFAS and a score of 2.34 for the EFAS for the Batulayang Tourism Village. Where these results occupy quadrant V and a suitable strategy for the Batulayang tourist village is to penetrate the market and develop products.